Functional Connectivity and Networks Underlying Complex Tool-Use Movement in Assembly Workers: An fMRI Study - Taniguchi, Seira; Higashi, Yuichiro; Kataoka, Hirotaka; Nakajima, Hiroshi; Shimokawa, Tetsuya (Frontiers in Human Neuroscience, 2021)
The aim of this study was to identify the functional connectivity and networks utilized during tool-use in real assembly workers. These brain networks have not been elucidated because the use of tools in real-life settings is more complex than that in experimental environments. We evaluated task-related functional magnetic resonance imaging in 13 assembly workers (Trained Workers, TW) and 27 age-matched volunteers (Untrained Workers, UTW) during a tool-use pantomiming task, and resting-state functional connectivity was also analyzed. Two-way repeated-measures analysis of covariance was conducted with the group as a between-subject factor (TW > UTW) and condition (task > resting) as a repeated measure, controlling for assembly time and accuracy as covariates. We identified two patterns of functional connectivity in the whole brain within three networks that distinguished TW from UTW. TW had higher connectivity than UTW between the left middle temporal gyrus and right cerebellum crus II (p-FDR = 0.002) as well as between the left supplementary motor area and the pars triangularis of the right inferior frontal gyrus (p-FDR = 0.010). These network integrities may allow for TW to perform rapid tool-use. In contrast, UTW showed a stronger integrity compared to TW between the left paracentral lobule and right angular gyrus (p-FDR = 0.004), which may reflect a greater reliance on sensorimotor input to acquire complex tool-use ability than that of TW. Additionally, the fronto-parietal task control network was identified as a common network between groups. These findings support our hypothesis that assembly workers have stronger connectivity in tool-specific motor regions and the cerebellum, whereas UTW have greater involvement of sensorimotor networks during a tool-use task.